2007
DOI: 10.1002/elps.200600719
|View full text |Cite
|
Sign up to set email alerts
|

Chip‐LC‐MS for label‐free profiling of human serum

Abstract: The discovery of biomarkers in easily accessible body fluids such as serum is one of the most challenging topics in proteomics requiring highly efficient separation and detection methodologies. Here, we present the application of a microfluidics-based LC-MS system (chip-LC-MS) to the label-free profiling of immunodepleted, trypsin-digested serum in comparison to conventional capillary LC-MS (cap-LC-MS). Both systems proved to have a repeatability of approximately 20% RSD for peak area, all sample preparation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…[103][104][105][106][107][108][109][110][111][112][113] Among these methods, optical and electrochemical methods are the most frequently utilized due to their selectivity and sensitivity. Other than the above major methods, approaches such as nuclear magnetic resonance (NMR) spectroscopy, [114][115][116][117][118] magnetoresistive, 119 and acoustical 120,121 are also coupled to microfluidics for sensing application.…”
Section: Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[103][104][105][106][107][108][109][110][111][112][113] Among these methods, optical and electrochemical methods are the most frequently utilized due to their selectivity and sensitivity. Other than the above major methods, approaches such as nuclear magnetic resonance (NMR) spectroscopy, [114][115][116][117][118] magnetoresistive, 119 and acoustical 120,121 are also coupled to microfluidics for sensing application.…”
Section: Detection Methodsmentioning
confidence: 99%
“…To date, several MS configurations have already been developed to be integrated with microfluidic devices for this application, for instance, electrospray ionization (ESI)-MS (Refs. 104-106) and matrix-assisted laser desorption ionization (MALDI)-MS. [107][108][109] In 2006, another paradigm is ion trap mass spectrometry integrated with microfluidics for protein identification by Hardouin et al 111 Other systems were also reported, such as a chip-liquid chromatography (LC)-MS system for labelfree profiling of human serum 113 and a LC-ESI-MS system for multiple proteins detection from breast cancer cellular extract. 112 The resolving ability of MS has recently been pushed down to the detection of a single molecular by Roukes's group in Caltech using a nanoelectromechanical system-based MS (NEMS-MS) (Fig.…”
mentioning
confidence: 99%
“…The overall performance of the microfluidic chip enabled a gradient liquid chromatographic separation and MS/MS identification of peptides with an estimated detection sensitivity of 5 to 7 fmol, demonstrated with both a plant and the human tissue sample (50). Horvatovich et al compared label-free profiling of immunodepleted, trypsin-digested serum by a microfluidics-based LC-MS system with a conventional capillary LC-MS system (18). The chip-LC-MS system had a two-times-higher resolution on the LC dimension and resulted in a lower average charge state of the tryptic peptide ions generated in the ESI interface than the cap-LC-MS while requiring about 30-times-less sample (18).…”
Section: Improved Sample Handling Through Chip-based Methodsmentioning
confidence: 99%
“…These use microfluidics-based technology for high-pressure nanoflow LC-MS systems, and incorporate the sample purification, separation and electrospray interface on a single chip thus allowing the processing of lower volume samples with complete automation of the analysis procedure and the possibility of screening based applications [80,81,82].…”
Section: Assessment Of Mass Spectral Approaches For the Detection Of mentioning
confidence: 99%